Multi-agent optimization of electricity markets participation portfolio with NPSO-LRS - Faia, Ricardo (2021)
The increasing unpredictability of electricity market prices as reflection of the renewable generation variability brings a new dimension to risk formulation, since market participation risk should consider the prices variation in each market. This paper proposes a new portfolio optimization model, considering a new approach for risk management. The problem of electricity allocation between different markets is formulated as a classic portfolio optimization problem with the consideration of the market prices forecast error as integral part of the risk asset. The multi-objective problem leads, however, to a heavy computational burden, and for this reason the method of weighting singlecriterion objectives is applied in this paper. A particle swarm optimizationbased metaheuristic is applied in order to enable decreasing the execution time of the optimization, while guaranteeing a good quality of results. A case study based on real data from the Iberian electricity market demonstrates the advantages of the proposed approach to increase market players’ profits while minimizing the market participation risk